(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research entitled (the Quranic story, its characteristics and goals) is an analytical study on the story in the Holy Qur’an and its characteristics and determination. The first section includes the define of the story and the retelling in terms of language and terminology, then I have defined in the first part, the story in terms of language and terminology and the second part I have defined the retelling language in terms of language and terminology. In the second section, I have mentioned the characteristics of the story in the Qur’an and the most important that include: 1- Focusing on the aspects which includes lessons with a good intention, and to avoid the useless ones. 2- The disparity in showing in terms of long and short stories. 3- The lessons and the sermon are confined to show the Quranic stories, so remember separated. 4- Repeating the stories indicate eloquence and miraculous features. 5- Mental convincing, and in the stories of the Qur’an the privacy of dialogue, as dialogue is a means of convincing. 6- The story in the Qur’an is one of the most prominent meanings of miracles, in terms of telling it about the previous nations, which was not known. In the third section, I talked about the issue of repeating the story in the Qur’an and the benefit of that regarding the wisdom and perception of that. The fourth section is devoted to mentioning the goals of the Quranic story, such as proving creed and monotheism, confirming the benefits of the Prophet, peace and blessings be upon him, and mitigating the violate of his people, by mentioning the stories of the previous prophets, dissemination the guidance of religion and clarifying them, consolidating the basic rules of religion, refuting suspicions and replying them, with an indication of the fundamentals of the call to Allah, and keeping the remnants of the prophets alive and commemorating them, and the debating with the People of the Scripture with the argument in what they concealed including evidence and guidance, In conclusion, the most important results reached by research and recommendations were mentioned